2018
DOI: 10.3390/nano8100783
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of Superhydrophobic Surface-Functionalized TiO2 Nanotubes to Corrosion and Intense Cavitation

Abstract: The availability of robust superhydrophobic materials with the ability to withstand harsh environments are in high demand for many applications. In this study, we have presented a simple method to fabricate superhydrophobic materials from TiO2 nanotube arrays (TNTAs) and investigated the resilience of the materials when they are subjected to harsh conditions such as intense cavitation upon ultrasonication, corrosion in saline water, water-jet impact, and abrasion. The TNTAs were prepared by anodization of Ti f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 72 publications
(74 reference statements)
0
11
0
Order By: Relevance
“…A vibrational spectrum of ODPA monolayer functionalized TiO 2 nanotubes was collected to validate the successful chemical functionalization of TiO 2 NTs surface with ODPA molecules (Figure 4a). The FTIR spectrum of ODPA functionalized TiO 2 exhibits a characteristic IR absorption band at 2848 and 2917 cm −1 due to symmetric and anti-symmetric C–H stretching vibrations of CH 2 in alkyl chain of ODPA [35,36,39]. The IR peak at 3019 cm −1 was derived from C–H stretch of terminal methyl (–CH 3 ) groups.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A vibrational spectrum of ODPA monolayer functionalized TiO 2 nanotubes was collected to validate the successful chemical functionalization of TiO 2 NTs surface with ODPA molecules (Figure 4a). The FTIR spectrum of ODPA functionalized TiO 2 exhibits a characteristic IR absorption band at 2848 and 2917 cm −1 due to symmetric and anti-symmetric C–H stretching vibrations of CH 2 in alkyl chain of ODPA [35,36,39]. The IR peak at 3019 cm −1 was derived from C–H stretch of terminal methyl (–CH 3 ) groups.…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, the effect of incorporation of different concentrations of discrete TiO 2 NTs on the physicochemical characteristics and permeation properties of the polyethersulfone (PES) membranes are reported. In addition, bare TiO 2 nanotubes are superhydrophilic and can be rendered superhydrophobic or amphiphobic if needed by suitable surface functionalization [35,36].…”
Section: Introductionmentioning
confidence: 99%
“…The reason is that toughness increases due to TNTs nanoarchitecture. Moreover, it has been reported that 100 nm diameter TNTs are hydrophobic [ 27 , 28 ] and thereof they block the water uptake in the overlap region.…”
Section: Resultsmentioning
confidence: 99%
“…When the weight ratio of modified-ZnO to fluorinated polysiloxane was 13:7, the contact angle of nanocomposite coating was 166°, and a sliding angle of 4°, was coating surface with hierarchical micro/nano-structures. Hua et al [ 22 ] presented a simple method to fabricate superhydrophobic materials from TiO 2 nanotube arrays (TNTAs). The hydrophilic TNTAs were functionalized with octadecyl phosphonic acid (ODPA) or 1H, 1H′, 2H, 2H′-perfluorodecyl phosphonic acid (PFDPA) to form a self-assembled monolayer on the TNTA surface to produce superhydrophobic ODPA@TNTA or PFDPA@TNTA surfaces.…”
Section: Introductionmentioning
confidence: 99%